A Case of Euglycemic Diabetic Ketoacidosis in a Patient With Type 2 Diabetes Mellitus and COVID-19 - Morrison, Nathan (Cureus, 2020)
Diabetic ketoacidosis (DKA) can cause significant morbidity and mortality in patients with type 1 or type 2 diabetes mellitus. DKA causes an approximate annual hospitalization rate of 6.3% and in-hospital case-fatality rate of 0.4%. A subset of DKA cases termed euglycemic diabetic ketoacidosis (eu-DKA) is characterized by euglycemia (<200 mg/dL), high anion gap metabolic acidosis, and an increased plasma ketone concentration. This clinical syndrome comprises approximately 2.6% to 3.2% of total DKA admissions, making it a rare condition. In this case report, a male patient was diagnosed with coronavirus disease 2019 (COVID-19) three days prior to arriving at the emergency department. Upon evaluation, he displayed severe acidemia and was diagnosed with eu-DKA. He was started on intravenous regular insulin and D5 one-half normal saline, which markedly improved his metabolic status. Notably, his admission was uncomplicated by respiratory symptoms of COVID-19. It is proposed that his eu-DKA was catalyzed by his recent COVID-19 infection. Recent studies that have shown COVID-19 may increase lipolysis and induce ketogenesis in susceptible patients.